О композитологии: предмет и задачи изучения - Неделяева-Степонавичене, С. И. (Kalbotyra, 1988)
The aim of the present article is to prove the autonomy of compounds and to show the difference between compositology (the linguistic science or compounds) and derivatology (the linguistic science of derivation).